Tekst jako „anastylos". Przedmiot i ciało w twórczości Jarosława Marka Rymkiewicza - Wojda, Dorota (Przestrzenie Teorii, 2007)
Text as Anastylos aims at reconstructing Jarosław Marek Rymkiewicz's poetics as well as his worldview. The present author sees them as inseparable orders. The category of anastylos, primarily describing a type of architectonic conservation is used here as a means of presenting the specificity of negative testimony given by Rymkiewicz to various forms of existence, inscribed by him into various genological forms and treated as the integrative factor in the entirety of his discourse. The author claims that the specificity of the negative testimony may be, in general terms, described as an effect of simultanuous identity and nonidentity between the text and the being it reconstructs as well as a presentation of its objects - a thing and a body - as related in an act of their mutual creation.